Factors Influencing High School Students' Decision to Pursue Undergraduate Studies in Thailand - Suwannapong, Apinya (Chalermkarnchana Academic Journal, 2025)
This study aims to analyze the factors influencing high school students' decision to pursue undergraduate education in Thailand. It focuses on five key aspects: personal factors, family influence, economic conditions, institutional factors, and government policies. A mixed-methods research approach was employed, combining quantitative data from 384 survey respondents and qualitative insights from in-depth interviews with relevant stakeholders. The findings reveal that institutional and personal factors have the greatest influence on students' decisions, particularly curriculum quality (Mean = 4.35) and interest in the chosen field of study (Mean = 4.32). Additionally, parental support (Mean = 4.45) plays a crucial role among family factors. The availability of scholarships (Mean = 4.02) was found to have a greater impact than general educational expenses, while government policies (Mean = 3.97) had a moderate influence on students' choices. The study suggests that (1) universities should enhance curriculum relevance to labor market demands and improve career counseling services, (2) families should play a more active role in supporting students' educational decisions, and (3) the government should improve the accessibility of scholarships and develop more flexible financial support mechanisms for students. These findings provide insights for educational policymakers and institutions to promote higher education enrollment in Thailand.